2013
DOI: 10.1002/elps.201200661
|View full text |Cite
|
Sign up to set email alerts
|

Interactomic approach for evaluating nucleophosmin‐binding proteins as biomarkers for Ewing's sarcoma

Abstract: Nucleophosmin (NPM) is a novel prognostic biomarker for Ewing's sarcoma. To evaluate the prognostic utility of NPM, we conducted an interactomic approach to characterize the NPM protein complex in Ewing's sarcoma cells. A gene suppression assay revealed that NPM promoted cell proliferation and the invasive properties of Ewing's sarcoma cells. FLAG-tag-based affinity purification coupled with liquid chromatography-tandem mass spectrometry identified 106 proteins in the NPM protein complex. The functional classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our protein profiles consistently identified 90 proteins regulated by EWS/FLI1 expression across four ES cell lines. A proteomic study using ES surgical samples identified high protein expression of NPM1 and confirmed that the expression was significantly associated with tumor malignancy and the prognosis in ES patients [ 18 , 23 ]. In our profiles of proteins associated with the inhibition of EWS/FLI1, NPM1 was also identified as a downregulated protein.…”
Section: Discussionmentioning
confidence: 95%
“…Our protein profiles consistently identified 90 proteins regulated by EWS/FLI1 expression across four ES cell lines. A proteomic study using ES surgical samples identified high protein expression of NPM1 and confirmed that the expression was significantly associated with tumor malignancy and the prognosis in ES patients [ 18 , 23 ]. In our profiles of proteins associated with the inhibition of EWS/FLI1, NPM1 was also identified as a downregulated protein.…”
Section: Discussionmentioning
confidence: 95%
“…biology. Previously, we investigated the proteins interacting with nucleophosmin, a prognostic biomarker for Ewing's sarcoma discovered by proteomics 19) , and identified novel prognostic proteins 20) , suggesting the utility of interactome approach to biomarker discovery. Although a previous study demonstrated the interaction of SBP1 with glutathione peroxidase 1 selenoprotein in colorectal cancer cells 12) , comprehensive studies of the SBP1 protein complex in cancer have yet to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry analysis revealed that elevated NPM expression could potentially predict poor prognosis in Ewing's sarcoma. Later, Haga et al . reported that NPM promoted the growth and invasion of Ewing's sarcoma cells and was bound to a number of proteins implicated in other malignancies, as evidenced by the interactome approach.…”
Section: Proteomics In Ewing's Sarcoma Researchmentioning
confidence: 99%